2017
DOI: 10.5539/ijb.v10n2p1
|View full text |Cite
|
Sign up to set email alerts
|

Learning a Behavioral Sequence: An Accessible Challenge for Myrmica sabuleti Workers?

Abstract: We aimed to investigate on the ability of the ant Myrmica sabuleti in learning a behavioral sequence. We created two sequences consisting in navigating through five successive elements on the way to the nest, and tried to learn them to foragers. They could progressively learn a sequence for which the different steps were presented in a backward order. Doing so, each exhibited step leaded to an already known step and thus to the reward consisting in finally entering the nest. The ants were unable to learn a beh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 17 publications
1
2
0
Order By: Relevance
“…We also showed that the ants could very obviously acquire serial recognition when receiving some reward together with the correct sequence during about four days, even reaching a maximum score of 60% after 7 training days. These results agreed with two previous ones according to which the ants could perform a behavioral sequence (Cammaerts & Cammaerts, 2018a) and recognize a correct sequence (Cammaerts & Cammaerts, 2018b) when the correct sequences were located during training in front of the nest or the sugar tube entrance, thus when being rewarded after having performed or moved along the sequence. The here shown ants' serial recognition acquisition is thus, finally an operant conditioning.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…We also showed that the ants could very obviously acquire serial recognition when receiving some reward together with the correct sequence during about four days, even reaching a maximum score of 60% after 7 training days. These results agreed with two previous ones according to which the ants could perform a behavioral sequence (Cammaerts & Cammaerts, 2018a) and recognize a correct sequence (Cammaerts & Cammaerts, 2018b) when the correct sequences were located during training in front of the nest or the sugar tube entrance, thus when being rewarded after having performed or moved along the sequence. The here shown ants' serial recognition acquisition is thus, finally an operant conditioning.…”
Section: Discussionsupporting
confidence: 82%
“…We recently approached this topic in the ant Myrmica sabuleti Meinert 1861. We first addressed response chaining, and showed that ants could learn a behavioral sequence when being rewarded at the end of the sequence, and that the last act of the sequence was better learned than the previous ones (Cammaerts M.-C. and Cammaerts R., 2018a). We then addressed serial recognition, and showed 1. that the ants could recognize a correct sequence made of three or four elements, given the choice between a correct and two or three wrong sequences, when being rewarded during the training, and 2. that the last element of the sequence was the best memorized (Cammaerts M.-C. and Cammaerts R., 2018b).…”
Section: Introductionmentioning
confidence: 99%
“…This kind of behavior is not unforeseen since workers of this ant possess several cognitive abilities. Among others, they can recognize themselves in a mirror though having probably no self-awareness, solve simple problems (e.g., walking around a barrier), learn to react to novel situations (e.g., pulling on a double door), learn a behavioral sequence, and can acquire serial recognition, but only if rewarded [ 28 , 29 , 30 , 31 , 32 ]. They can present an acquired conditional behavior in a subsequent situation (e.g., having been conditioned at the same time to a cue associated with meat and to another cue associated with sugar water, when deprived of meat, they react to the cue that was previously associated with meat, and when deprived of sugar water, they react to the one that was previously associated with sugar water [ 33 ]).…”
Section: Introductionmentioning
confidence: 99%